Late Holocene environment of subalpine northeastern Taiwan from pollen and diatom analysis of lake sediments. (15th December 2015) - Wang, Liang-Chi; Behling, Hermann; Kao, Shuh-Ji; Li, Hong-Chun; Selvaraj, Kandasamy; Hsieh, Meng-Long; Chang, Yuan-Pin
Highlights: Taiwan pollen/diatom records indicate varied EASM and typhoon over past 3500 years. Estimated lake levels and diatom-inferred pH revealing cold and dry at 3.5–2 ka BP. The last 2k records can be linked well to varied SSTs of WPWP and ENSO events. Abstract: We used multi-decadal pollen and diatom records from sediment core TFL-1 from Tsuifong Lake to reconstruct the vegetation dynamics and hydroclimate in northeastern Taiwan during the past 3500 cal BP. Coarse grained sediments in association with higher percentages of wetland pollen (Cyperaceae) and upper conifer pollen ( Tsuga and Pinus ) in the lower part of the core indicate low lake levels and a relatively cold/dry climate between 3500 and 2030 cal BP, reflecting a decline of the East Asian summer monsoon (EASM). Muddy sediments coupled with reduction of wetland pollen represent the rise of lake levels, implying the re-strengthening of the EASM during the past 2000 years. Paleotemperature was inferred from the variation of pollen origin from the upper and lower mountain forest, indicating the global temperature anomalies of the Medieval Warm Period (MWP) and the Little Ice Age (LIA). In comparison to the main climate forces in the North Pacific, we suggest that the long-term climatic trend in Taiwan was controlled by variations in EASM intensity, while increased precipitation over the past 2000 years may also be linked to warmer sea surface temperature (SST) of the western Pacific Warm Pool (WPWP) and increased El Niño-Southern Oscillation (ENSO) events, which increased typhoon intensity. Higher diatom-inferred pH during 2930–2030 cal BP and the LIA suggest strong hydrological disturbances, reflecting more typhoons passing over Taiwan. The frequent typhoon events could be linked by an abrupt shift of typhoon track, due to the reduction of the WPWP and expansion of the Northwestern Pacific High, which move typhoons in a more westerly direction.